Análisis de los desafíos tecnológicos que enfrenta el periodismo radial en la ciudad de Babahoyo - Ayala Romero, Stephany Ivonne (2020)
The present case study was based on the radial media of the city of Babahoyo in order to analyze the current technological challenges that they face. The techniques used to carry out this work were: bibliographic information and interviews with radio owners and journalists who work in this area, which allowed to obtain accurate and first-hand data. This document reflects the use of the new technologies that journalism professionals do, the positive and negative that can occur when using these new forms of transmission. The radios in Babahoyo are still analog, but with the help and contributions of the technology base you can be at the forefront of communication. The radio will never die as such, as long as it is fed with all the technology it will be much better.